2003
DOI: 10.1017/s0021859603003344
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of nitrogen use efficiency of cauliflower I. A simulation modelling based analysis of nitrogen availability under field conditions

Abstract: Data from several field experiments (eight crops grown under a widely varying nitrogen supply on a loess loam soil) were used for a simulation modelling based analysis of nitrogen availability of cauliflower. The model was built out of components describing root growth, nitrate transport to the roots and the vertical nitrate transport within the soil.Root observations obtained over 2 years indicated an increased fraction of dry matter allocated to the fine roots under N deficiency. An adopted version of a root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Researchers at John Innes Institute studied P-use efficiency in B. oleracea [40][41][42] and showed that there is genetic variation in this trait and that it is under quantitative control [42]. Cauliflower varieties with proportionally more fine roots have been shown to be more N-use efficient [43].…”
Section: Nutrient-use Efficiencymentioning
confidence: 99%
“…Researchers at John Innes Institute studied P-use efficiency in B. oleracea [40][41][42] and showed that there is genetic variation in this trait and that it is under quantitative control [42]. Cauliflower varieties with proportionally more fine roots have been shown to be more N-use efficient [43].…”
Section: Nutrient-use Efficiencymentioning
confidence: 99%
“…The submodels which describe the water movement through the soil and evapotranspiration were presented in detail by Kage et al (2003) and Kage (2000). Roughly, the water transport model calculates soil water movement by using the water-content-based formulation of the Richard's equation.…”
Section: Water Transport and Evapotranspirationmentioning
confidence: 99%
“…Another possibility to save N fertilizer is a more precise prediction of the N demand. For this purpose, models predicting the time course of cauliflower growth (Alt et al 2000), soil N availability for cauliflower N uptake (Kage et al 2003) or the time course of N uptake of white cabbage and Brussel sprouts Feller 1998, 2001) have been developed. A further approach which was hardly investigated yet is the breeding of N-efficient genotypes, which are characterized by a low susceptibility in yield to reduced N fertilization levels (Schenk 2006).…”
Section: Introductionmentioning
confidence: 99%